2019
DOI: 10.1002/macp.201900292
|View full text |Cite
|
Sign up to set email alerts
|

Generating Triple Crystalline Superstructures in Melt Miscible PEO‐b‐PCL‐b‐PLLA Triblock Terpolymers by Controlling Thermal History and Sequential Crystallization

Abstract: The morphology, crystallization behavior, and properties of multi‐crystalline polymer systems based on triple crystalline biodegradable PEO‐b‐PCL‐b‐PLLA triblock terpolymers are reviewed. The triblock terpolymers, with increasing poly(l‐lactide) (PLLA) content, exhibit a triple crystalline nature. Upon cooling from melt, the PLLA block crystallizes first and templates the spherulitic morphology of the terpolymer. Then, the poly(ε‐caprolactone) (PCL) block crystalizes and, finally, the poly(ethylene oxide) (PEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 90 publications
(188 reference statements)
0
16
0
Order By: Relevance
“…To that purpose, model triblock terpolymers of PLLA, PCL, and PEO blocks (PEOb-PCL-b-PLLA) have been exhaustively studied. 4,[33][34][35][36] Particularly, the morphology of these melt miscible and triple crystalline triblock terpolymers have been reported by Chiang et al 37 and Palacios et al 33,35,36 Wide-angle X-Ray scattering (WAXS) measurements, carried out during cooling, confirmed that the PLLA block is the one that crystallizes first, followed by the PCL and lastly, the PEO. PLOM observations indicated that the microscale structure is templated by the PLLA block as a result of its crystallization.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…To that purpose, model triblock terpolymers of PLLA, PCL, and PEO blocks (PEOb-PCL-b-PLLA) have been exhaustively studied. 4,[33][34][35][36] Particularly, the morphology of these melt miscible and triple crystalline triblock terpolymers have been reported by Chiang et al 37 and Palacios et al 33,35,36 Wide-angle X-Ray scattering (WAXS) measurements, carried out during cooling, confirmed that the PLLA block is the one that crystallizes first, followed by the PCL and lastly, the PEO. PLOM observations indicated that the microscale structure is templated by the PLLA block as a result of its crystallization.…”
Section: Introductionmentioning
confidence: 67%
“…The PEO-b-PCL-b-PLLA is a triblock terpolymer with an alternating superstructure of three crystalline phases, as we had reported in previous publications. 4,[33][34][35][36] The PLLA block ) was employed as a single catalyst. For more details on the synthesis procedure and characterization, refer to 60,61 , and the references in them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of a third potentially crystallizable block to diblock copolymers results in a more complex analysis of the crystallization behavior. Few studies have been published about tricrystalline triblock terpolymers, such as ABC-type triblock terpolymers and ABCBA pentablock terpolymers, including the apolar PE block, and the polar PEO, PCL, and PLLA blocks [ 17 , 24 , 37 , 42 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…Palacios et al studied the crystallization and morphology of ABC triblock terpolymers with three crystallizable blocks: PEO, PCL, and PLLA [ 92 , 93 , 94 , 95 ]. They [ 92 ] highlighted the triple crystalline nature of the PEO- b -PCL- b -PLLA triblock terpolymer, with the three different blocks crystallizing independently upon cooling from the melt.…”
Section: Introductionmentioning
confidence: 99%